Congenital absence of the appendix in a 21-year-old male with clinical presentation of acute appendicitis: a diagnostic challenge at Prince Ali Military Hospital - Bawaneh, Mohannad K.; Alshoubaki, Wael I.; Alzboon, Moath R.; Hamiedah, Murad; Alnawaiseh, Hussien; Albtoush, Basel; Foqahaa, Ibrahim Al (International Journal of Advances in Medicine, 2024)
Acute appendicitis is commonly associated with right lower quadrant abdominal pain and is a leading cause of emergent abdominal surgeries, carrying a significant morbidity risk. The rarity of anatomical deviations, such as appendix agenesis, complicates diagnosis and can exacerbate clinical outcomes due to diagnostic delays or mismanagement. We report the case of a 21-year-old male, who was surgically explored at prince Ali military hospital for suspected acute appendicitis based on clinical symptoms and an Alvarado score of 7. Despite strong clinical indications, imaging studies, including ultrasound and computed tomography, failed to visualize the appendix. Intraoperatively, appendix agenesis was confirmed, a finding seldom reported in medical literature. This case underscores the challenges of diagnosing congenital appendix absence and highlights the need for heightened awareness among clinicians to prevent unnecessary surgical interventions. Such awareness could potentially improve patient outcomes by sparing them from unnecessary surgical risks and complications.